Parental Knowledge on Prevention of Early Childhood Caries and the Effectiveness of a Leaflet Intervention - Elkarmi, Rawan; AlJafari, Ahmad; Haddad, Sarah; Al Soud, Dina (Jordan Medical Journal, 2024)
Background: Parental education on child oral health plays an important role in caries prevention. Leaflets are a means of delivering educational messages. This study aims to evaluate the efficacy of leaflets in improving parental knowledge on prevention of early childhood caries. Methods: This was a cross-sectional study. Parents of children younger than six years attending a pediatric clinic at a large hospital were asked to complete a questionnaire that noted their sociodemographic characteristics, oral hygiene practices, and knowledge on prevention of early childhood caries, which was given a score out of 20. After reading an educational leaflet, a follow-up phone interview was conducted to evaluate any improvement in parental knowledge. ANOVA and McNemar’s tests were used for statistical analysis. Results: Three hundred and ninety-one parents participated in the study. The average knowledge score pre-intervention was 6.4 out of 20. Approximately 10% of parents were regular dental attenders. Around 12% of parents were aware of the correct age of the child’s first dental visit and the correct age to start tooth brushing; 20.5% knew about fluoride varnish; 7.2% understood that sugar-containing snacks should be consumed all at once; and, less than 50% believed that regular dental visits prevent caries. After reading the leaflet, there was a statistically significant improvement in almost all variables evaluating parents’ knowledge on prevention of early childhood caries. Conclusion: Knowledge on prevention of early childhood caries among this sample of parents was very poor. Leaflets were successful in improving parental knowledge. There is a need to distribute such leaflets in healthcare centers and hospitals and to evaluate their efficacy further by comparison with other means.